2020
DOI: 10.31557/apjcp.2020.21.12.3697
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin Apoptotic Effects on T47D Breast Cancer Cells is a P53-Independent Approach

Abstract: Objective: Using nutraceuticals in cancer therapy is a strategy contributing with other approaches to promote apoptosis in cancer cells. Myricetin is a polyphenol flavonoid that forms main ingredients of various type of foods and beverages. The inducing properties of myricetin in apoptosis is reported by several investigations. The present study aimed to assess apoptotic effects of myricetin on T47D breast cancer cells and to evaluate part of the mechanisms of action. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…LncRNA-ENST00000421645 was overexpressed in a T lymphocyte line (Jurkat-E6-1), and lncRNA-ENST00000421645 was found to promote the expression of the apoptosis-related protein caspase3 in T lymphocytes and promote T lymphocyte apoptosis. Caspase3 is a major effector caspase and is a common downstream effector molecule of multiple apoptotic pathways that plays a central role in the process of apoptosis; thus, it is called a “death executing protease ( Li et al, 1997 ; Porter and Jänicke, 1999 ; Winstel et al, 2019 ; Soleimani and Sajedi, 2020 ). Our findings suggested that lncRNA-ENST00000421645 induced apoptosis in T lymphocytes through the caspase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA-ENST00000421645 was overexpressed in a T lymphocyte line (Jurkat-E6-1), and lncRNA-ENST00000421645 was found to promote the expression of the apoptosis-related protein caspase3 in T lymphocytes and promote T lymphocyte apoptosis. Caspase3 is a major effector caspase and is a common downstream effector molecule of multiple apoptotic pathways that plays a central role in the process of apoptosis; thus, it is called a “death executing protease ( Li et al, 1997 ; Porter and Jänicke, 1999 ; Winstel et al, 2019 ; Soleimani and Sajedi, 2020 ). Our findings suggested that lncRNA-ENST00000421645 induced apoptosis in T lymphocytes through the caspase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Myricetin-induced cell apoptosis has been observed in T47D breast cancer cells, associated with increased expression of apoptotic genes including caspase-3, -8, -9, BAX/Bcl-2, p53, BRCA1, and GADD45. In particular, the BRCA1-GADD45 pathway was involved in the apoptotic death of the T47D cells [141]. Myricetin has also been reported to inhibit the migration and invasion of hepatocellular carcinoma MHCC97H cells and weaken filopodia and lamellipodia [142].…”
Section: Myricetinmentioning
confidence: 99%
“…Bax, Caspase-3, Caspase-8, Caspase-9, p53, BRCA1, GADD45, and E-Cad Prostate [132], ovarian [133], skin [134], breast [135,139], liver [136,137,140], colorectal [138], and thyroid [141] cancer ↓ PIM1, CXCR4, MDR-1, Bcl-2, VEGFR2, p38, p-STAT3, COX2, IL-6, TNF-α, NFκB, and N-Cad…”
mentioning
confidence: 99%
“…Previous studies have demonstrated the anti-oxidant, antiviral, antibacterial, and anticancer effects of myricetin (10)(11)(12). Myricetin has been found to exhibit anticancer effects against pancreatic (13), liver (14), prostate (15), thyroid (16) and breast cancer (17)(18)(19) in vitro. In particular, myricetin targets the mitochondrial apoptosis pathway to inhibit cellular proliferation and induce apoptosis (20).…”
Section: Introductionmentioning
confidence: 99%